PENGARUH KEPEMIMPINAN, KOMPETENSI, MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN IMPLIKASI TERHADAP KINERJA KARYAWAN - Nida, Sofwatun; Husainah, Nazifah; Maswanto, Maswanto; Ananto, Tri (Taksasila Edukasi Insani, 2024)
This study aims to explore the influence of leadership, competence, and work motivation on job satisfaction and employee performance at PT. Amorojo Putra Pewaris, a leading construction services company. Using a quantitative approach with survey methods, this research collected data through questionnaires distributed to the company's employees. Data analysis was conducted using multiple linear regression to test the proposed hypotheses. The research findings show that leadership, competence, and work motivation significantly positively affect employee job satisfaction. Additionally, job satisfaction has been proven to have a significant positive impact on employee performance. This study underscores the importance of effective leadership, good competence management, and high work motivation in enhancing job satisfaction and employee performance, ultimately positively affecting the overall company performance.